Behavior of Laser Ablation Plasma During Transport in Multicusp Magnetic Field Using Different Targets for Laser Ion Source. (December 2017) - Takahashi, Kazumasa; Uchino, Takumi; Ikegami, Keisuke; Sasaki, Toru; Kikuchi, Takahashi; Harada, Nob.
Abstract: To obtain laser ion sources with high current and long pulse, a method of applying multicusp magnetic fields to confine laser ablation plasmas has been proposed. The behaviors of the laser ablation plasmas during transporting in the multicusp magnetic fields are investigated by experiments using two types of multicusp magnetic field and the targets of aluminum, copper, and lead. To understand the behavior of the ablation plasma, numerical calculations for ion trajectory were also performed. The results indicate that the distance which a plasma proceeds until the appearance of the effect of the magnetic field on the plasma behavior at the center axis could be explained by ion motions affected by the azimuthal magnetic field.